Relation Between Sickle Cell Disease and Depression and Anxiety Symptoms in Children - بدرة رواء; مازن غالية; عبد المنعم غانم (Latakia University Journal -Medical Sciences Series, 2023)
Objective: Investigating a relation between Sickle Cell Disease as a chronic disease and Anxiety and Depression symptoms in children, and Studying the factors affecting these symptoms. Patients and methods: An analytic Case-Control study that included a total of 78 children ;38 with SCD aged 8-14 years and 38 matched control children with no chronic diseases ,who had been hospitalized in Pediatric Department in Tishreen University Hospital between June 2021 and July 2022 . Children with Cerebral Palsy ,Mental Retardation ,Autistic Spectrum , Attention-Deficit Hyperactivity Disorder and Hearing or Speech Disorders which interfere child answering scales were excluded from the study. Depression symptoms was measured by: DEPRESSION SELF-RATING SCALE FOR CHILDREN (Birleson 1978). Anxiety symptoms was measured by: Spence Children’s Anxiety Scale – Self report(SCAS). We detected the effective factors on Depression and Anxiety symptoms in children with SCD by analyzing Demographic and clinical and laboratory variables. Results: Children with SCD had significantly higher Birleson Depression Scale mean scores (P=0,004).And 3(7,9%) of children with SCD and 0(0%) of control group had clinical depression symptoms but the differences was not statistically significant (P=0,08). Children with SCD had significantly higher Spence Anxiety Scale mean scores (P=0,004).And, 24(63,2%) of children with SCD and 16(42,1%) of control group had clinical Anxiety symptoms and the differences was statistically significant (P=0,04) ; particularly the occurrence of Separation Anxiety symptoms and Physical Injury fears (P=0,001 , P=0.0001) We found that the Demographic variables had no effect on Depression and Anxiety symptoms in children with SCD .However, by analyzing clinical and laboratory variables We detected that complications related to SCD particularly Acute chest syndrome, also the number of painful crises in the past 1 year are effected factors in Depression and Anxiety symptoms in children with SCD. Conclusion: Children with SCD are at high risk to developing Depression .However, Anxiety disorders are more common in Children with SCD particularly Separation Anxiety and Physical Injury fears .And The most important effective factors are SCD complications particularly Acute chest syndrome and the high frequency of painful crises.